2017
DOI: 10.1016/j.brat.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol on emotion in social drinkers

Abstract: Understanding why people drink alcohol and in some cases develop drinking problems has long puzzled researchers, clinicians, and patients alike. In the mid-1940s and early 1950s, experimental research began to systematically investigate alcohol’s hedonic properties. Presumably, alcohol consumption would prove reinforcing as a consequence of its capacity either to relieve stress or to brighten positive emotional experiences. This article reviews experimental research through the years examining the impact of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 165 publications
(249 reference statements)
8
85
0
Order By: Relevance
“…In Scotland specifically, whilst 29% of drinkers surveyed reported that they had been drinking more-often since the beginning of lockdown, the same percentage reported they were drinking less-often ( Alcohol Focus Scotland, 2020 ). Whilst there is evidence to suggest that alcohol-dependant individuals drink to alleviate negative emotional states ( Koob, 2011 ), the relationship between emotional experience and alcohol in social drinkers is less-clearly defined ( Sayette, 2017 ). Poor mental health has consistently been reported in abusive ( Pottenger et al, 1978 ; Grant and Harford, 1995 ; Schuckit, 2006 ) and social drinkers ( Birnbaum et al, 1983 ; Parker et al, 1987 ; Jones et al, 2007 ), and drinking alcohol has been associated with negative mood ( Howland et al, 2010 ; Alford et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Scotland specifically, whilst 29% of drinkers surveyed reported that they had been drinking more-often since the beginning of lockdown, the same percentage reported they were drinking less-often ( Alcohol Focus Scotland, 2020 ). Whilst there is evidence to suggest that alcohol-dependant individuals drink to alleviate negative emotional states ( Koob, 2011 ), the relationship between emotional experience and alcohol in social drinkers is less-clearly defined ( Sayette, 2017 ). Poor mental health has consistently been reported in abusive ( Pottenger et al, 1978 ; Grant and Harford, 1995 ; Schuckit, 2006 ) and social drinkers ( Birnbaum et al, 1983 ; Parker et al, 1987 ; Jones et al, 2007 ), and drinking alcohol has been associated with negative mood ( Howland et al, 2010 ; Alford et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because alcohol consumption is a well-known regulator of emotions (Fairbairn & Sayette, 2014;Lowe et al, 2013;Sayette, 2017;Sayette, Creswell, et al, 2012) and mood can be altered via social influences (Neumann & Strack, 2000;Parkinson & Simons, 2009;Sy, Côté, & Saavedra, 2005). Moreover, there is a growing body of evidence to suggest that risk-taking is shaped by the mood people are in (Kim & Kanfer, 2009;Yuen & Lee, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This previous research suggests acute alcohol administration selectively reduces response when these stressors are unpredictable, regardless its source, but we have yet to consider the impact of chronic AOD use in these tasks in a clinical sample. Other researchers have recently noted that the effects of alcohol on response to unpredictable stressors in social drinkers also appear to extend beyond manipulations of electric shock to more real world situations that include inherent unpredictability, such as in most social interactions (e.g., Sayette, 2017;see Fairbairn & Sayette, 2014 for review).…”
Section: Individual Differences In Possible Stress Neuroadaptationmentioning
confidence: 99%